Tim William Machan (ed.), Vafþrúðnismál [with an introduction and notes] - Edlund, Lars-Erik (Journal of Northern Studies, 2010)
Review of: Tim William Machan (ed.), Vafþrúðnismál [with an introduction and notes], 2nd edition, Toronto: Centre for Medieval and Renaissance Studies, Durham University, Pontifical Institute of Mediaeval Studies 2008 (Durham Medieval and Renaissance Texts 1), ISBN 9780888445612, 142 pp.